Pengaruh Layanan Bimbingan Kelompok terhadap Kemandirian Pengambilan Keputusan pada Pemilihan Karir Siswa Kelas VIII di SMPN 1 Pangkalan Berandan - Khairina Ulfa Syaimi; Nurmairina Nurmairina (Journal on Education, 2023)
This study aims to determine the effect of group counseling services on the independence of decision making in the career selection of class VIII students at SMPN 1 Pangkalan Berandan. The research method used is a quasi-experimental nonequivalent control group design. The experimental group received treatment in the form of 6 group guidance sessions which were held once a week. The control group received no treatment.The population in this study were Grade VIII students of SMPN 1 Pangkalan Berandan, class of 2021. The sampling technique used was non-probability sampling in the form of purposive sampling. The students who were sampled in this study were 20 people with decision making score on career selection in the low category. The instrument used in determining the sample of this study is the instrument for making decisions on career selection with five choices on a Likert scale consisting of 35 valid items with a reliability using Cronbach's alpha of 0.857. Statistical data analysis techniques were performed using descriptive statistics using empirical mean to see the average pretest and posttest scores in the experimental group and the control group.Hypothesis testing was carried out using the Wilcoxon signed rank test, by comparing the gain scores from the posttest and pretest in the experimental group and the control group. The results of hypothesis testing show that the Asymp. Sig is 0.003, which means that through the results of these calculations it is concluded that sig 0.003 <0.05, meaning that the increase in decision-making independence in career selection for Class VIII students at SMPN 1 Pangkalan Berandan is the treatment group higher than the control group.